2021
DOI: 10.1002/adma.202100625
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐Triggered Self‐Healing Flexible Perovskite Photodetectors with Excellent Mechanical Stability

Abstract: low-temperature solution method, which makes it a promising candidate for flexible devices. [19][20][21][22][23] Novel devices based on perovskite have proven great potential for further application. [24][25][26] However, perovskites are very sensitive to air moisture which invades cracks of flexible films and accelerates the damage to devices. In the base of environmental protection, the toxicity of lead also demands for long working life for perovskite devices to avoid the disposal of lead waste. [27][28][29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 47 publications
0
76
0
Order By: Relevance
“…As an ew kind of multifunction materials,o rganicinorganic hybrid perovskites (OIHPs) with chemical designability,s tructural diversity,l ow-cost and low-temperature solution-processability have been widely concerned in many fields, [1,2] such as solar cells, [3,4] nonlinear optics (NLO), [5,6] ferroelectrics, [7,8] light emitting diodes [9,10] and photodetectors. [11][12][13] Meanwhile,OIHPs not only have the obvious grains and grain boundaries like ceramics,b ut also possess the rotation of organic ions like polymer.A mong these,c hiral OIHPs with asymmetric centers have exceptional attractive properties,s uch as circular dichroism, [14,15] chiroptoelectronics, [16] optical rotation, [16] second-harmonic generation (SHG), [5] and ferroelectricity, [17,18] which have attracted more and more attentions in many fields.The influence of chirality on the properties of OIHPs is mainly focused on the chiralitydependent circular photogalvanic effect, [19,20] spin transport, [21] optical selection rules [22] and chirality-induced ferroelectrics. [23] Due to the inherent noncentrosymmetry of chiral OIHPs,which endowing the chiral OIHPs produce asecondorder doubling frequency response by NLO effects.F urthermore,anideal NLO crystal must satisfy two conditions,one is non-centrosymmetric and the other one is phase matching (PM).…”
Section: Introductionmentioning
confidence: 99%
“…As an ew kind of multifunction materials,o rganicinorganic hybrid perovskites (OIHPs) with chemical designability,s tructural diversity,l ow-cost and low-temperature solution-processability have been widely concerned in many fields, [1,2] such as solar cells, [3,4] nonlinear optics (NLO), [5,6] ferroelectrics, [7,8] light emitting diodes [9,10] and photodetectors. [11][12][13] Meanwhile,OIHPs not only have the obvious grains and grain boundaries like ceramics,b ut also possess the rotation of organic ions like polymer.A mong these,c hiral OIHPs with asymmetric centers have exceptional attractive properties,s uch as circular dichroism, [14,15] chiroptoelectronics, [16] optical rotation, [16] second-harmonic generation (SHG), [5] and ferroelectricity, [17,18] which have attracted more and more attentions in many fields.The influence of chirality on the properties of OIHPs is mainly focused on the chiralitydependent circular photogalvanic effect, [19,20] spin transport, [21] optical selection rules [22] and chirality-induced ferroelectrics. [23] Due to the inherent noncentrosymmetry of chiral OIHPs,which endowing the chiral OIHPs produce asecondorder doubling frequency response by NLO effects.F urthermore,anideal NLO crystal must satisfy two conditions,one is non-centrosymmetric and the other one is phase matching (PM).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the obvious shifts of Pb 4f 7/2 and 4f 5/2 peaks also verified the strong interaction between SHP and Pb 2+ [4b] . Besides, as a consequence of the incorporation of SHP additive, the binding energy of I 3d 3/2 and 3d 5/2 became smaller than that without SHP, indicating a high electronegativity in Figure 3 d [11c] . Therefore, attributing to these synergistic interactions of SHP, enhanced crystallinity with oriented growth were achieved [18]…”
Section: Resultsmentioning
confidence: 58%
“…In comparison with the pristine precursor solution, SHP provided the crystallographic templates and increased the critical concentration ( C c , representing the difficulty of nucleation), contributing to the passivation defects and enlarged crystal grains. Besides, SHP can passivate iodine (I − ) vacancy to compensate for the electronic loss at the grain boundary, thus prevents the electrons from being captured by the defects and reduces recombination [11c, 15] …”
Section: Resultsmentioning
confidence: 99%
“…Top‐view SEM images in Figure 1d, e demonstrate an enlarged grain size for the perovskite film after adding 0.10 mg mL −1 PU without changing the crystal phase (XRD patterns of perovskite films in Figure S3) and film thickness (cross‐sectional SEM images in Figure S4), but large dosage (such as 0.50 mg mL −1 PU) has a negative effect on the morphology (Figure S5) and optical absorbance (Figure S6). Considering that uniformly distributed PU can function as a three‐dimensional skeleton to support the perovskite growth, the intrinsic mechanism for improved film quality is mainly attributed to the interaction between PU and PbI 2 or PbBr 2 , such as the formation of hydrogen bonds (−N−H⋅⋅⋅X−Pb−X), [26, 27] to slow down the crystallization speed. By combining the increased photoluminescence (PL) intensity and prolonged carrier lifetime obtained from the time‐resolved PL (TRPL) spectra in Figure S7, it is concluded that the nonradiative recombination induced by detrimental defects in the perovskite film is significantly suppressed for maximizing the photovoltaic performances [28]…”
Section: Figurementioning
confidence: 99%